The Dilemma Between Shareholder Value and Long-term Business Sustainability - Muslim, Muslim (Advances in Management & Financial Reporting, 2025)
Purpose: This study investigates the tension between short-term shareholder value creation and long-term business sustainability in publicly traded companies. It explores how firms balance the pressure for immediate financial returns with the need to invest in sustainable practices for future viability. Research Design and Methodology: The research employs a Systematic Literature Review (SLR) methodology, analyzing existing literature on strategic frameworks such as ESG integration, strategic agility, and shared value creation. The study synthesizes insights from relevant academic sources to comprehensively understand how companies manage the conflict between short-term and long-term objectives. Findings and Discussion: The findings reveal that companies often prioritize short-term profits due to shareholder pressure, which can hinder long-term sustainability efforts. However, firms that adopt strategic agility and integrate ESG into their core strategies are better equipped to navigate future risks and maintain competitiveness. The study also highlights the effectiveness of shared value creation in helping companies align profitability with social and environmental responsibilities, demonstrating that sustainability practices contribute to long-term shareholder value. Implications: This study offers practical implications for corporate management, emphasizing the need for a balanced approach that meets both short-term financial goals and long-term sustainability. It calls for increased transparency, stakeholder engagement, and adopting integrated reporting to enhance corporate accountability. Future research could further explore how smaller firms and industries address this dilemma.